Spectroscopy Profiling of Trunking Sago Palm (Metroxylon sagu Rottb.) using Nuclear Magnetic Resonance (NMR) - Yan, Wei Jie (Universiti Malaysia Sarawak, UNIMAS, 2010)
Sago palm (Metroxylon sagu Rottb.) is one of the important agricultural plants which contribute to the economy of Malaysia with an export value of RM 51.407 million at the year 2007. Major sago palm plantations in Malaysia are located at Sarawak state which consists of 56,916 hectares at the year 2007. The export value of sago palm is dependent on its sago starch locates in its trunk. In cultivation of sago palm, there are some sago palms which show phenotypic expression of non-trunking that eliminated the value of the plant. Genomic expression study of the sago palm is a method to identify the genes that regulates the trunking phenotype which can be represented by its metabolites. This study was done to measure the variation of metabolites in trunking sago palm whether it shows significance in the same trunking phenotype sago palms population. M. sagu metabolites were extracted using extraction method based on Sobolev (2005), with certain adaptation. Result from nuclear magnetic resonance, thin layer chromatography and infrared analysis shows that there are no differences between the NMR spectroscopy metabolites pattern in the trunking sago palm trees. Result comparison with non-trunking sago palm NMR spectroscopy metabolite pattern variances shows that the variances are insignificance.